ANEMIA AND HEART FAILURE - Cvetković, Zorica; Marinković, Gligorije; Bukurecki, Ilija; Marković, Olivera (Srpski medicinski časopis Lekarske komore, 2024)
The presence of anemia in patients with heart failure is a significant independent adverse prognostic factor. The etiology of anemia is multifactorial and the nature of heart failure itself, advanced age, and frequent comorbidities contribute to its development. Notably, absolute or functional iron deficiency, even in the absence of anemia, significantly diminishes the quality of life, increases hospitalization frequency, and raises mortality rates in patients with heart failure. The intricate etiology and pathophysiology of anemia present a challenge for the accurate interpretation of laboratory parameters of iron metabolism and necessitate a tailored therapeutic approach.
Keywords: anemia; heart failure; etiology; treatment